Behind the increasing erosion problem: The role of local institutions and social capital on coastal management in Argentina - Rojas, Mara Leticia (2014)
Coastal ecosystems are one of the most impacted and altered regions worldwide, both because of natural reasons and because of the large population that is concentrated along the coasts. In Argentina, the problem of coastal erosion is very important as these areas represent the 18.33% of the whole territory with 36% of population living in this area. The objective of the present article is to characterize the main problems related to the use of resources and coastal management, leading to coastal erosion, from the perceptions of stakeholders and decision makers in the coastal zone of Pehuén Co and Monte Hermoso, Argentina. The fieldwork was performed by participative methodologies, while the results were analyzed under the institutional and social capital theoretical framework. One of the main results of the paper is that the lack of a strong social capital in the region and the existence of formal monitoring and sanctioning procedures developed by distant governmental institutions have increased the overexploitation of coast and beaches. Notwithstanding, the current and future relevance of coastal erosion for the region will demand the elaboration of bottom-up policies to reduce the vulnerability of the region and the performance of the adaptation policies.